Ecosystem‐Level Energy and Water Budgets Are Resilient to Canopy Mortality in Sparse Semiarid Biomes. Issue 10 (29th September 2020) - Huang, Cheng‐Wei; Krofcheck, Dan J.; Duman, Tomer; Fox, Andrew M.; Pockman, William T.; Lippit, Christopher D.; McIntire, Cameron D.; Litvak, Marcy E.
Abstract: Climate‐driven woody vegetation mortality is a defining feature of semiarid biomes that drives fundamental changes in ecosystem structure. However, the observed impacts of woody mortality on ecosystem‐scale energy and water budgets and the responses of surviving vegetation are highly variable among studies in water‐limited environments. A previous girdling manipulation experiment in a piñon‐juniper woodland suggested that although ecosystem‐scale evapotranspiration was not altered by large‐scale piñon mortality, soil water content decreased and the surviving juniper experienced greater water stress than juniper in an undisturbed woodland. Here we experimentally explored to what extent mortality‐induced changes in energy balance components can explain these results. We compared energy fluxes measured above two adjacent piñon‐juniper woodlands where piñon girdling was implemented at one site and the other subsequently experienced large‐scale natural piñon mortality. We found that the mortality‐induced decrease in canopy area was not sufficient to alter surface reflectance, roughness, and partitioning between energy budget components at both sites. A radiative transfer model estimated that because of the sparse premortality canopy, surface reflectance is more sensitive to a large increase in understory leaf area than further loss of crown area. Increased water stress in the remaining juniper following both mortality events can be explained by an increase in radiation on the ground that promoted higher soil temperature and evaporation. We found similar responses of ecosystem and tree‐level functions to both girdling and natural mortality. This suggests that girdling is an appropriate approach to explore the impact of tree mortality on ecosystem structure, function, and energy balance. Key Points: Piñon mortality in piñon‐juniper woodlands did not alter surface reflectance and roughness that can largely impact energy and water budgets Enhanced incoming radiation on the ground following mortality increased soil evaporation and water stress in surviving juniper Responses of ecosystem function and surviving juniper to piñon mortality were similar between the girdling‐induced and natural mortality